Growth through adversity: posttraumatic growth in anonymous living liver donors. Issue 8 (10th April 2022) - Krause, Sandra; Pritlove, Cheryl; Abbey, Susan; Jung, Judy
Abstract: Purpose: Post-traumatic growth (PTG) is positive change that occurs after struggling with challenging life crises. Research on PTG has typically been limited to oncology populations, first-responders, and individuals in warzones. We report the experience of PTG amongst a sample of 26 anonymous live liver donors. Methods: Anonymous donors were those with no biological connection or prior relationship with recipients. Twenty-six participants participated in a semi-structured qualitative interview examining their experience with, and outcomes of donation. Interview transcripts were analyzed for themes about PTG using the constant comparison method. Results: While some donors indicated that donation had little lasting impact on their life, most cited significant personal and interpersonal changes resulting from the experience. The most common positive changes included deepened bonds with others, appreciation for personal strength, clearer life direction, legacy-building, and a connection to the transplant community. Conclusion: Despite the short-term physical trauma of living donor surgery, the act of anonymous donation appeared to be a catalyst for positive long-term psychological growth. These findings help to bolster the ethical argument in favour of anonymous donation. IMPLICATIONS FOR REHABILITATION: There is a shortage of organ donors for recipients in need, and anonymous living liver donors can successfully reduce wait times and mortality rates for those on wait lists. There are some questions about the ethics of anonymous donation due to possible negative physical and psychological effects of donation surgery on donors. In a qualitative study, this study shows that donors ascribe significant meaning to, and derive many psychological benefits from, their donation experience. These findings provide insights about how to best support anonymous donors through and after their donation experience.